Sistem Kendali Level Ketinggian Air Berbasis Fuzzy Control Menggunakan Simulink - Fani Kurniawan; Yulian Zetta Maulana; Risa Farrid Christianti (Techné : Jurnal Ilmiah Elektroteknika, 2022)
Today's technology shows very significant developments in automation systems. Filling water in a tank is a process that is widely used in the oil industry. The process of filling and draining water in a closed water tank will raise difficulty for the operator to control the water level in the tank. Therefore, we will create a system to control the water level using a fuzzy controller. To get the value of fuzzification from the difference in the value of the set point and defuzzification connected to the motor pump. Fuzzy design system was obtained by making methods, fuzzification, defuzzification, and rules. The use of ultrasonic sensors during the experiment caused a spike in value because the ultrasonic sensor had not detected water but had no significant effect on the response to altitude levels. When the valve is opened, the controller has an effect on the resulting response. The more the valve is opened, the worse the response will be but the system remains stable. The fuzzy output will be connected to the PLC which will be connected to the Kepserver and tank to regulate the flow rate to the tank. Matlab is connected with PLC devices using Kepserver. The best performance is found in the 2× reduction valve opening response test with a fuzzification range of 8000-24000 while the performance value of time rise is 66.458 s, settling time is 110 s, steady state error is -2%, and overshoot is 9%.